Mini Solar Power Supply for Night Market Hawker - Muhammad Hihdir, Muhammad Aiman; Mohammad Radzi , Nur Hanis (Evolution in Electrical and Electronic Engineering, 2021)
A mini solar power supply is a power supply unit that can generate electricity and provide power within a specified time frame. Hawkers require electricity to operate their night markets, so a traditional generator is used to generate electricity. The traditional generator is large and cumbersome to transport. In addition, traditional generators required petrol to operate, which increases the cost of fuel for hawkers, and the disadvantage of using fuel is that it produces smoke, which contributes to air pollution. Hence, a mini solar power supply could be the answer for hawkers, as it does not require any fuel and lightweight. This project aims to replace the use of traditional generators to generate electricity for night market operations by night market hawkers. The main goals of this project are to develop a mini solar power supply using a solar photovoltaic panel to power USB ports, LED lamps, and other electrical appliances. A 12V battery was used to power the mini solar power supply, which was powered by a 50W solar panel controlled by a solar charger controller. In comparison to a traditional generator, solar energy was stored in a 12V rechargeable battery, and the mini solar power supply is lightweight. The developed system’s results successfully demonstrated that the concept is viable and that it could be scaled up to a larger scale in the solar industry. The system has the potential to be useful in solar generator technology due to its energy autonomy and low cost.